Evaluation of teaching factory policy implementation with CIPP evaluation model - Ary Sunaryo; Widiyanti Widiyanti; Nunung Nurjannah (Research and Social Study Institute, 2021)
The purpose of this study is to use the evaluation model of SMKN 1 Boyolangu Tulungagung Context, Input, Process, Product (CIPP) to determine the suitability of the application of Teaching Factory (TEFA) in overcoming job problems such as unemployment. This research was conducted using the CIPP assessment method by searching for data using observation, interviews, and questionnaire data collection. Data analysis used a descriptive percentage system. The survey results show that the assessment of the implementation of the Teaching Factory (TEFA) program conducted at SMKN 1 Boyolangu Tulungagung using the CIPP model, which is highly standardized and produces an average percentage of conformity of 89%. However, these results are issued with a note that teachers must have expertise in their respective operational fields in the Teaching Factory (TEFA).